PROSPEK GEOPARK NASIONAL KARANGSAMBUNG-KARANGBOLONG TERHADAP LIMA KAWASAN EKOWISATA DI KABUPATEN KEBUMEN PROVINSI JAWA TENGAH - Hapsari, Dwi Meita; Ardiansyah, Bayu Krisna (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2020)
Development of the Earth Park (Geopark) which requires good governance in the development of the Geopark Area in Karangsambung-Karangbolong, Kebumen Regency, East Java Province. Good governance will create the development of geological heritage that is able to develop tourist areas are also supportive. The purpose of this research is to study and analyze how to develop Geopark and government efforts to overcome the inhibiting factors in an effort to empower people around the Geopark Area. The method used in this research is qualitative research with descriptive and inductive evaluation methods. Data collection techniques through observation, documentation, and interviews. The results obtained indicate that the results of the development of the Karangsambung-Karangbolong National Geopark continue to be pursued in qualifications towards an international Geopark in 2021. The author provides suggestions for achieving the qualification target Geopark needed synergy from various related parties, active participation of the community to participate in any activities that are the construction of Geopark.